Chinese Locative Verbs of Movement - Lister, Anthony C. (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1988)
In Chinese there are two main methods of expressing the idea of the English directional preposition to. Certain Chinese verbs are followed directly by a placeword and the English preposition has a zero equivalent. Other verbs generally require the interposition of a so-called locative verb. The status of the latter is ambiguous since on the one hand it plays a functional grammatical role while on the other it retains its verbal meaning. In addition, one of two directional conplements, qù 'to go' and lài 'to come' may follow the placeword. If, as it is widely believed, these directional complements in certain structures assume the role of the main verb, then the normal word order is reversed and the main verb follows the placeword, rather than preceding it.